Utilization of the Education Report Card as Data-Based Planning in Primary Schools - Subekti, Yelli Ari; Wardani, Danik Eka; Retnowati, Nunung Kurnia; Nurkolis, Nurkolis (Lembaran Ilmu Kependidikan, 2024)
Utilization of Education Report Cards as Data-Based Planning in Primary Schools is an important document that contains information about the development and learning achievements of students at school. In the context of data-based planning in primary schools, report cards can be used as a rich source of information to analyze needs, develop programs, and make appropriate decisions. This study aims to examine the utilization of report cards as data-based planning in primary schools. The method used is mixed methods by analyzing report card data, interviews and documentation in three primary schools. The results showed that report cards can be utilized as a data source to: Identifying student learning needs based on competency achievements; Developing learning programs that are in accordance with student needs; Evaluating the effectiveness of learning programs that have been implemented; Making strategic decisions to improve the quality of education in primary schools. Utilizing report cards as data-based planning can help primary schools make more informed, effective and accountable decisions. This can contribute to improving the quality of learning and student achievement.